Populations of western North American monkeyflowers accrue niche breadth primarily via genotypic divergence in environmental optima. Issue 10 (22nd October 2022) - Coughlin, Aeran O.; Wooliver, Rachel; Sheth, Seema N.
Abstract: Niche breadth, the range of environments that individuals, populations, and species can tolerate, is a fundamental ecological and evolutionary property, yet few studies have examined how niche breadth is partitioned across biological scales. We use a published dataset of thermal performance for a single population from each of 10 closely related species of western North American monkeyflowers (genus Mimulus ) to investigate whether populations achieve broad thermal niches through general purpose genotypes, specialized genotypes with divergent environmental optima, and/or variation among genotypes in the degree of generalization. We found the strongest relative support for the hypothesis that populations with greater genetic variation for thermal optimum had broader thermal niches, and for every unit increase in among‐family variance in thermal optimum, population‐level thermal breadth increased by 0.508°C. While the niche breadth of a single genotype represented up to 86% of population‐level niche breadth, genotype‐level niche breadth had a weaker positive effect on population‐level breadth, with every 1°C increase in genotypic thermal breadth resulting in a 0.062°C increase in population breadth. Genetic variation for thermal breadth was not predictive of population‐level thermal breadth. These findings suggest that populations of Mimulus species have achieved broad thermal niches primarily through genotypes with divergent thermal optima and to a lesser extent via general‐purpose genotypes. Future work examining additional biological hierarchies would provide a more comprehensive understanding of how niche breadth partitioning impacts the vulnerabilities of individuals, populations, and species to environmental change. Abstract : Niche breadth, the range of environments that individuals, populations, and species can tolerate, is a fundamental ecological and evolutionary property, yet few studies have examined how niche breadth is partitioned across biological scales. We use a published dataset of thermal performance for a single population from each of 10 closely related species of western North American monkeyflowers (genus Mimulus ) to investigate whether populations achieve broad thermal niches through general‐purpose genotypes, specialized genotypes with divergent environmental optima, and/or variation among genotypes in the degree of generalization. We found that populations accrue niche breadth primarily via genotypic divergence in environmental optima, and to a lesser extent through general‐purpose genotypes.